Effects of Staff Turnover on Continuity of Care in Pediatric Chronic Disease Management - Das, Debattri; Chakrabarty, Tarpan; Halder, Arjama (Journal of Neonatal Surgery, 2025)
Continuity of care is a critical factor in the effective management of chronic diseases among pediatric patients. This study investigates the impact of staff turnover—particularly among physicians, nurses, and allied health professionals—on the quality and consistency of care provided to children with long-term medical conditions such as asthma, diabetes, and cystic fibrosis. Conducted as a mixed-methods study in three tertiary care pediatric hospitals, the research analyzes quantitative data on turnover rates and treatment adherence over a two-year period, supplemented by qualitative interviews with healthcare providers and caregivers. Findings reveal a significant correlation between high staff turnover and disruptions in care plans, reduced caregiver satisfaction, increased medical errors, and lower treatment adherence among pediatric patients. Interviews further underscore the emotional and psychological burden placed on families due to frequent changes in care teams, which undermine trust and hinder communication. The study concludes that implementing targeted retention strategies—such as structured mentorship, workload management, and team-based care models—can enhance staff stability and, by extension, improve health outcomes in pediatric chronic disease management. These findings offer valuable insights for hospital administrators and policymakers aiming to strengthen pediatric care delivery through workforce stabilization.